2002
DOI: 10.1161/01.cir.0000022664.21832.5d
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of Coronary Artery Calcium Quantity Measured by Electron Beam Computed Tomography in Asymptomatic Adults

Abstract: Background-Electron beam computed tomography is an accurate, noninvasive method to detect and quantify coronary artery calcification (CAC), a marker of subclinical and clinical coronary artery atherosclerosis. CAC quantity predicts future coronary artery disease end points in asymptomatic adults, but measured risk factors explain less than half the variability in CAC quantity. Although several candidate genes for CAC have been identified, the relative importance of genetic influences on CAC quantity has not be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
77
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 117 publications
(87 citation statements)
references
References 36 publications
6
77
4
Order By: Relevance
“…28 Also, it has been shown that some additional variability of CAC scores can be explained by genetic diversity which was not considered in the current study. 29,30 The most important risk factor determinants of CAC score were age and male sex, followed by current smoking, systolic blood pressure, and non HDL-cholesterol. Diabetes was relatively rare in both cohorts, in particular in ECAC.…”
Section: Risk Factor Associations With Cacmentioning
confidence: 99%
“…28 Also, it has been shown that some additional variability of CAC scores can be explained by genetic diversity which was not considered in the current study. 29,30 The most important risk factor determinants of CAC score were age and male sex, followed by current smoking, systolic blood pressure, and non HDL-cholesterol. Diabetes was relatively rare in both cohorts, in particular in ECAC.…”
Section: Risk Factor Associations With Cacmentioning
confidence: 99%
“…Subjects were participants in the Functional Arterial Changes in Atherogenesis Study which is examining the relationship of arterial function measures to subclinical disease measures and cardiovascular risk factors in non-Hispanic white subjects participating in the community-based Epidemiology of Coronary Artery Calcification (ECAC) study [23]. The ECAC study is an ongoing study of the pathogenesis of coronary artery calcification in Rochester, Minnesota.…”
Section: Study Populationmentioning
confidence: 99%
“…Protocols at baseline and follow-up were identical, as described previously. 17,18 Dual scan runs were obtained for all participants examined in 1993 and later; 138 participants examined before 1993 had one scan run at baseline.…”
Section: Electron-beam Ct Measures Of Cacmentioning
confidence: 99%